PROPOSED MARKETING STRATEGY FOR KAI ACCESS APPLICATION (CASE STUDY IN BANDUNG) (The Indonesian Journal of Business Administration, 2019)
PT. KAI released an official application called KAI Access, where there are several products and features that are only available in the application. However, the sale of train tickets in the KAI Access application is under other online travel agent applications. The researcher conducts internal analysis that consists of segmenting, targeting and positioning analysis, and marketing mix analysis. On external analysis consists of porter’s five forces analysis, competitor analysis, and customer analysis. The primary data of this research is customer analysis through questionnaire. The result is each variable of marketing mix has a significant influence on customer satisfaction except place and people. Each variable of marketing mix except price does not have a significant direct effect on customer loyalty, and customer satisfaction can significantly affect customer loyalty. Then SWOT (strength, weakness, opportunity and threats) analysis is carried out based on internal and external analysis, after doing SWOT analysis is continued by doing root cause analysis. The result of root cause analysis is There are three main factors which cause lack of selling, which is external, internal and promotion.  And the last, the researcher make marketing strategy recommendation by using TOWS analysis based on SWOT analysis. Keywords:Application, Customer Loyalty, Customer Satisfaction, KAI Access, Marketing Mix, Price Promotion